BiSeNet V2: Bilateral Network with Guided Aggregation for Real-Time Semantic Segmentation - Yu, Changqian; Gao, Changxin; Wang, Jingbo; Yu, Gang; Shen, Chunhua; Sang, Nong (International journal of computer vision, 2021)
Low-level details and high-level semantics are both essential to the semantic segmentation task. However, to speed up the model inference, current approaches almost always sacrifice the low-level details, leading to a considerable decrease in accuracy. We propose to treat these spatial details and categorical semantics separately to achieve high accuracy and high efficiency for real-time semantic segmentation. For this purpose, we propose an efficient and effective architecture with a good trade-off between speed and accuracy, termed Bilateral Segmentation Network (BiSeNet V2). This architecture involves the following: (i) A detail branch, with wide channels and shallow layers to capture low-level details and generate high-resolution feature representation; (ii) A semantics branch, with narrow channels and deep layers to obtain high-level semantic context. The detail branch has wide channel dimensions and shallow layers, while the semantics branch has narrow channel dimensions and deep layers. Due to the reduction in the channel capacity and the use of a fast-downsampling strategy, the semantics branch is lightweight and can be implemented by any efficient model. We design a guided aggregation layer to enhance mutual connections and fuse both types of feature representation. Moreover, a booster training strategy is designed to improve the segmentation performance without any extra inference cost. Extensive quantitative and qualitative evaluations demonstrate that the proposed architecture shows favorable performance compared to several state-of-the-art real-time semantic segmentation approaches. Specifically, for a 2048 × 1024 input, we achieve 72.6% Mean IoU on the Cityscapes test set with a speed of 156 FPS on one NVIDIA GeForce GTX 1080 Ti card, which is significantly faster than existing methods, yet we achieve better segmentation accuracy. The code and trained models are available online at https://git.io/BiSeNet .